A Decision-Making Modellingin Probabilistic ConditionUsingMonte-carloand Decision Tree AnalysisonUpstream Petroleum Business Development (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The upstream oil and gas industry has high risks, uncertainties and capital costs. An investment decision-makingmodel that considers risk and uncertainty analysis is needed to review the potential advantages and disadvantages of eachdevelopment scenario. In this study, a risk and sensitivity analysis was carried out to gain an understanding of the decisionproblem, then the Monte-carlo simulation and decision tree were applied to obtain the best scenario for the developmentupstream oil and gas business. From sensitivity analysis it is found that oil prices and production have the most dominantinfluence on NPV. In this research, monte-carlo simulation and decision tree can be combined to improve the quality ofanalysis and it is hoped that decision makers will have a complete picture with the proposed approach.